Build Character Culture Professional as Key HR Success towards Generation Powerful Gold Tough and Superior Competitiveness - Darmilisani; Ance Marintan D. Sitohang (International Journal of Business and Applied Economics, 2023)
Generation Gold is a smart generation comprehensive and character superior. The objective of the study is to answer and implementation from target and strategic Kemenristekdikti in increase relevance, quantity, and quality source Power educated human resources (HR). Study This uses exploration descriptive method with analysis build character culture professional as key success going to generate powerful gold competitive tough and superior. Research results show exists the role of important build competence of human capital and character of social culture entrepreneurship as key importance in determining enhancement of growth economy quality and power competitive nation.